IMPLEMENTASI WORK FROM HOME TUNTUTAN KEADAAN ATAU POTENSI DI MASA DEPAN? (Studi Kasus Pada Institusi Pendidikan Universitas Diponegoro Semarang) - Adli Mustaghfirin Anshor; Ismi Darmastuti (Faculty of Economics and Business Diponegoro University, 2022)
The COVID-19 pandemic that occurred at the end of 2019, brought major changes and had an impact on all elements of the world community. Over time, cases of COVID-19 transmission continue to increase. In order to reduce the number of transmissions, the Government issued a policy in the form of (Lockdown), limiting direct contact, and changing traditional work methods into Work From Home. But in its running, WFH raises pros and cons among employees. There are those who feel that during WFH productivity increases, on the contrary, there are also those who feel that WFH causes more stress than before. This study aims to find out in depth and understand further how working conditions are during the Pandemic, then this research will prove the impact felt by employees as a result of implementing Work From Home and find out more about the evaluation of its implementation. The research method used is qualitative with a case study approach to understand an event or case in more depth, as well as the use of the interview method as a data collection technique to fulfill the information needed in research.resource persons in this study were employees with differences in gender and employment status, with the object being the Personnel Section of Diponegoro University Semarang, which was expected to be able to provide clear and detailed answers. The results showed that, male employees felt more work productivity compared to female employees when carrying out Work From Home (WFH).